Ability Write Reading Summary - Agusnimar Gaurifa (Indonesian Journal of Education and Mathematical Science, 2022)
The data collection tool used was a written test, namely making a summary of the story of the legend of Malin Kundang, with assessment criteria, namely point 2 length of the summary, main idea, explanatory idea, use of words and sentences according to the contents of the summary with the reading. before the indicator is determined as a means of collecting research data, it is first validated by the three Indonesian language study teachers in a triangulation manner until it is declared fit for use. After the legend manuscript was administered to the respondent, it was processed statistically; with the results as the interval 71-85. Second, from the results of observations of the level of ability obtained information: 1) a description of student learning outcomes in learning obtained data, namely: students who have a high level of ability are 16 people or 40.504%, students who have a moderate level of ability are 9 people or 24.32%, students who have a low level of ability are 13 people or 34.14%. 2) a description of student learning outcomes for each item of question is obtained: for item 1 (ability level 36 people, and medium ability level 1 person), for item 2 (high ability level 22 people, medium ability level 7 people, low ability level 8 people ), for icon 3 (high ability level 24 people, medium ability level 5 people, low ability level 8 people), for item 4 (high ability level 25 people, medium ability level 6 people, medium ability level 7 people, low ability level 28 people) based on the description above, it can be concluded that the students' ability to write a narrative paragraph framework is classified as moderate. This statement is stated as moderate because of the variation in the abilities of students where there are good performers and some are low. So that to determine it, take the middle way, namely moderate.